Clinicomicrobiological Profile and Antibiotic Susceptibility Trends in Chronic Lacrimal Sac Infections in a Rural Indian Population (Ukrainian Journal of Ophthalmology, 2025)
Background: Chronic dacryocystitis, characterized by persistent inflammation and infection of the lacrimal sac and nasolacrimal duct, is a prevalent cause of ocular morbidity, particularly in rural India. Delayed diagnosis and inappropriate antibiotic use can result in recurrent infections and serious complications.Objective: To evaluate the bacteriological profile and antibiotic sensitivity patterns of chronic dacryocystitis cases in a rural tertiary eye care center, and to compare findings with previously reported data.Methods: This prospective observational study included 90 clinically diagnosed cases of chronic dacryocystitis from March 2011 to February 2012. Specimens were obtained using sterile techniques and subjected to aerobic culture. Isolates were identified through Gram staining and biochemical methods. “Antibiotic sensitivity was determined using the Kirby-Bauer disc diffusion technique. Statistical analysis was performed using Fisher’s exact test with significance set at p ≤ 0.05.Results: Culture positivity was observed in 73.33% of cases, with single organisms isolated in 63.33% and mixed growth in 10% .Staphylococcus aureus was the predominant Gram-positive isolate in adults, while Streptococcus pneumoniae was most frequent in pediatric cases. Gram-positive organisms comprised 78.58% of isolates; Gram-negative bacteria, including Pseudomonas aeruginosa and Klebsiella pneumoniae, accounted for 21.42%. Vancomycin and gatifloxacin showed the highest sensitivity among Gram-positive isolates, while amikacin was most effective against Gram-negative organisms. Culture-negative cases (15.56%) may be attributable to anaerobic pathogens not assessed in this study.Conclusion: Chronic dacryocystitis remains a significant health concern in rural India, with distinct bacteriological trends. Timely microbiological evaluation and sensitivity-guided antibiotic therapy are essential to prevent complications. Larger studies with anaerobic cultures are warranted for a more comprehensive microbial assessment.
Keywords: chronic dacryocystitis; lacrimal sac infection; rural ophthalmology; Staphylococcus aureus; Streptococcus pneumoniae; antibiotic sensitivity; vancomycin; amikacin; microbiological profile; ocular complications